Transforming the Medication Regimen Review Process Using Telemedicine to Prevent Adverse Events. Issue 2 (24th November 2020) - Kane‐Gill, Sandra L.; Wong, Adrian; Culley, Colleen M.; Perera, Subashan; Reynolds, Maureen D.; Handler, Steven M.; Kellum, John A.; Aspinall, Monica B.; Pellett, Megan E.; Long, Keith E.; Nace, David A.; Boyce, Richard D.
Abstract : Background/Objectives: Federally‐mandated consultant pharmacist‐conducted retrospective medication regimen reviews (MRRs) are designed to improve medication safety in nursing homes (NH). However, MRRs are potentially ineffective. A new model of care that improves access to and efficiency of consultant pharmacists is needed. The objective of this study was to determine the impact of pharmacist‐led telemedicine services on reducing high‐risk medication adverse drug events (ADEs) for NH residents using medication reconciliation and prospective MRR on admission plus ongoing clinical decision support alerts throughout the residents' stay. Design: Quality improvement study using a stepped‐wedge design comparing the novel service to usual care in a one‐year evaluation from November 2016 to October 2017. Setting: Four NHs (two urban, two suburban) in Southwestern Pennsylvania. Participants: All residents in the four NHs were screened. There were 2, 127 residents admitted having 652 alerts in the active period. Intervention: Upon admission, pharmacists conducted medication reconciliation and prospective MRR for residents and also used telemedicine for communication with cognitively‐intact residents. Post‐admission, pharmacists received clinical decision support alerts to conduct targeted concurrent MRRs and telemedicine. Measurement: Main outcome was incidence of high‐risk medication, alert‐specific ADEs. Secondary outcomes included all‐cause hospitalization, 30‐day readmission rates, and consultant pharmacists' recommendations. Results: Consultant pharmacists provided 769 recommendations. The intervention group had a 92% lower incidence of alert‐specific ADEs than usual care (9 vs 31; 0.14 vs 0.61/1, 000‐resident‐days; adjusted incident rate ratio (AIRR) = 0.08 (95% confidence interval (CI) = 0.01–0.40]; P = .002). All‐cause hospitalization was similar between groups (149 vs 138; 2.33 vs 2.70/1, 000‐resident‐days; AIRR = 1.06 (95% CI = 0.72–1.58); P = .75), as were 30‐day readmissions (110 vs 102; 1.72 vs 2.00/1, 000‐resident‐days; AIRR = 1.21 (95% CI = 0.76–1.93); P = .42). Conclusions: This is the first evaluation of the impact of pharmacist‐led patient‐centered telemedicine services to manage high‐risk medications during transitional care and throughout the resident's NH stay, supporting a new model of patient care.